TIMP3 c.319C>T, p.(Arg107Cys): Novel Sequence Variant In Sorsby Fundus Dystrophy - Hristova, Rozaliya; Veleva, Nevyana; Oscar, Alexander; Slavchev, Svetoslav; Zdravkov, Yani (Nepalese Journal of Ophthalmology, 2024)
Introduction: Sorsby fundus dystrophy is a rare autosomal dominant inherited retinal disease. The purpose of this case report is providing evidence to link the novel variant TIMP3 c.319C>T, p.(Arg107Cys), classified as variant of uncertain significance, to the clinical phenotype and to consider assignment of pathogenicity. Case: Thorough history and comprehensive ophthalmological exam of a 51-year old female with presenile cataract and difficulty in night vision were conducted. Visual acuity was 0.15 logMAR and 0.05 logMAR in the right and left eye, respectively. Observations: The examination was remarkable for pseudophakia in the left eye and bilateral drusenoid deposits. Visual fields demonstrated reduced retinal sensitivity. Optical coherence tomography showed drusen in the periphery. Fundus autofluorescence demonstrated corresponding hyper-autofluorescence. Electroretinography depicted reduced bioelectrical activity for scotopic conditions. Genetic testing identified a heterozygous missense, splice region variant TIMP3 c.319C>T, p.(Arg107Cys), which is a variant of uncertain significance and no other possible disease causing mutations. Conclusion: Based on our findings we propose assignment of pathogenicity to the novel variant TIMP3 c.319C>T, p.(Arg107Cys) as likely pathogenic in Sorsby Fundus Dystrophy.